Incentives and social relationships of hunters and traders in a Liberian bushmeat system. (September 2019) - Jones, Sorrel; Papworth, Sarah; Keane, Aidan; St John, Freya; Smith, Emmanuel; Flomo, Abraham; Nyamunue, Zuannah; Vickery, Juliet
Abstract: Hunting provides livelihoods and food security for a large number of people across the tropics but endangers wildlife populations. Effective management requires understanding both social and economic dynamics of local bushmeat systems, yet social elements such as relationships between actors are often overlooked. We provide the first detailed description of a rural hunting system in Liberia, from interviews with 205 hunters and 50 traders in the Gola Forest. We found bushmeat contributed substantially to local livelihoods and earnings from hunting and trading were high relative to local alternatives (median US120 and US262/month, hunters and traders respectively). Most of hunters' catch was sold to traders (85% of harvested biomass) and subsequently transported to urban markets (65% of all harvested biomass). Local consumption accounted for 27% of total harvest. Financial risks from meat confiscation were primarily born by traders, many of whom were women, and 60% perceived this as a motivation to reduce trading. By contrast, the most commonly stated motivation to reduce hunting was the time demanded by alternative activities such as farming. This discrepancy implies that livelihood support initiatives and law enforcement tools may play distinct roles across groups. Relationships between hunters and traders were complex and involved a variety of credit arrangements. Interpersonal trust played an important role, with mistrust of hunters being cited by 12% of traders as the principle barrier for profiting from bushmeat trade. Our findings provide context for designing conservation strategies and suggest that underlying social processes deserve closer attention in bushmeat research.